Stability Analysis of the Supercritical Surface Quasi-Geostrophic Equation - Yan Jia; Xingguo Gui; Bo-Qing Dong (Abstract and Applied Analysis)
This paper is devoted to the study of the stability issue of the supercritical dissipative surface quasi-geostrophic equation with nondecay low-regular external force. Supposing that the weak solution of the surface quasi-geostrophic equation with the force satisfies the growth condition in the critical BMO space , it is proved that every perturbed weak solution converges asymptotically to solution of the original surface quasi-geostrophic equation. The initial and external forcing perturbations are allowed to be large.